Influence of the lamina cribrosa on the rate of global and localized retinal nerve fiber layer thinning in open-angle glaucoma. Issue 14 (April 2017) - Park, Hae-Young Lopilly; Kim, Sung In; Park, Chan Kee
Abstract : Abstract: The advent of optical coherence tomography (OCT) imaging allows identification of the structural contribution of the lamina cribrosa (LC) to glaucoma progression. This study aimed to determine the role of various LC features, such as the LC depth (LCD), LC thickness (LCT), and focal LC defects, on the future rate of progressive retinal nerve fiber layer (RNFL) thinning in patients with glaucoma. One hundred eighteen patients with glaucoma who had undergone at least 4 OCT examinations were included. Features of LC, including the LCD, LCT, and presence of focal LC defects, from serial scan of the optic disc using the enhanced depth imaging of Spectralis OCT; were analyzed at baseline. Eyes were classified as those with or without progressive RNFL thinning using the guided progression analysis of Cirrus OCT. Factors associated with the rate of RNFL thinning (linear regression analysis against time for global average, inferior, and superior RNFL thicknesses, μm/year) were evaluated using a general linear model. Greater baseline LCD and thinner baseline LCT were significantly associated with the rate of superior RNFL thinning. Focal LC defects were significantly more frequent in eyes with progressive inferior RNFL thinning (93.8%) and the location of the focal LC defect was only related to the location of progression RNFL thinning in the inferior region ( P  < 0.001). A deeper and thinner LC was related to the rate of superior RNFL thinning, and the presence of focal LC defects was related to the rate of inferior RNFL thinning.